2019
DOI: 10.1042/cs20190587
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid oxidation inhibitor etomoxir suppresses tumor progression and induces cell cycle arrest via PPARγ-mediated pathway in bladder cancer

Abstract: Tumor cells rely on aerobic glycolysis as their main energy resource (Warburg effect). Recent research has highlighted the importance of lipid metabolism in tumor progression, and certain cancers even turn to fatty acids as the main fuel. Related studies have identified alterations of fatty acid metabolism in human bladder cancer (BCa). Our microarray analysis showed that fatty acid metabolism was activated in BCa compared with normal bladder. The free fatty acid (FFA) level was also increased in BCa compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 54 publications
2
74
0
Order By: Relevance
“…Peroxisome proliferator-activated receptors (PPARs), which are members of the nuclear receptor superfamily, can be divided into three subtypes: PPARα, PPARβ and PPARγ [5]. Our results and previous studies showed that PPARγ plays a significant role in the occurrence and progression of bladder cancer through regulation of proliferation, apoptosis, metastasis, and reactive oxygen species (ROS) and lipid metabolism [6][7][8][9][10]. The purpose of this paper is to provide an overview of the role, function and potential molecular mechanisms of PPARγ in bladder cancer.…”
Section: Introductionsupporting
confidence: 51%
See 3 more Smart Citations
“…Peroxisome proliferator-activated receptors (PPARs), which are members of the nuclear receptor superfamily, can be divided into three subtypes: PPARα, PPARβ and PPARγ [5]. Our results and previous studies showed that PPARγ plays a significant role in the occurrence and progression of bladder cancer through regulation of proliferation, apoptosis, metastasis, and reactive oxygen species (ROS) and lipid metabolism [6][7][8][9][10]. The purpose of this paper is to provide an overview of the role, function and potential molecular mechanisms of PPARγ in bladder cancer.…”
Section: Introductionsupporting
confidence: 51%
“…The mRNA expression of CPT1A was significantly higher in MIBC patients than in NMIBC patients [133]. In vivo and in vitro experiments by our group showed that etomoxir, a specific inhibitor of CPT1A, inhibited bladder cell proliferation and induced cell cycle arrest in G0/G1 phase by activating the PPARγ signaling pathway [6]. In addition, our results also revealed that simvastatin, an inhibitor of cholesterol synthesis, reduced intracellular cholesterol levels and inhibited cell proliferation and migration through the PPARγ signaling pathway [10].…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Increased glycolysis under normoxic conditions (Warburg effect), glutamine metabolism, and lipid metabolism are the main characteristics of malignant tumors. Previous studies have indicated that metabolic pathways play critical roles in the occurrence and progression of BC [4][5][6]. Therefore, it is indispensable to explore more potential reliable and valuable biomarkers, especially metabolism-associated genes (MAGs), to predict disease development and prognosis in BC patients.…”
Section: Introductionmentioning
confidence: 99%